BAYI TABUNG SEBAGAI SOLUSI INFERTILITAS PADA PASANGAN SAH: KAJIAN LITERATUR MEDIS DAN ETIS - Resti Rahmadika Akbar; Annisa Nazwa Wiedy; Insil Pendri Hariyani; Mutiara Anissa (Nusantara Hasana Journal, 2025)
In Vitro Fertilization (IVF) is an assisted reproductive technology that offers a significant solution for legally married couples experiencing infertility. This study aims to examine the medical, ethical, legal, and religious dimensions of IVF, including the use of emerging technologies such as Polygenic Embryo Screening (PES) and the practice of surrogacy. Medically, IVF is effective in addressing various infertility factors, yet it carries risks such as Ovarian Hyperstimulation Syndrome (OHSS), preeclampsia, and metabolic disorders, along with long-term health implications for offspring. Ethically, IVF raises debates regarding the moral status of embryos, the adequacy of informed consent, and concerns about eugenics through embryo selection. Legally, the lack of global harmonization in regulating surrogacy and gamete donation creates challenges in protecting the legal rights of children and intended parents. From an Islamic perspective, IVF is permissible if performed within a valid marriage using the couple’s own gametes, with strict prohibition against third-party involvement to preserve lineage and marital integrity. This study highlights the need for ethical and culturally sensitive regulatory frameworks and recommends further research on long-term health impacts of IVF, the effectiveness of informed consent, and global policy development for PES and surrogacy practices.